2020
DOI: 10.1038/s41598-020-66604-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis and identification of candidate genes for salt tolerance in rice by GWAS

Abstract: Soil salinity is a major factor affecting rice growth and productivity worldwide especially at seedling stage. Many genes for salt tolerance have been identified and applied to rice breeding, but the actual mechanism of salt tolerance remains unclear. In this study, seedlings of 664 cultivated rice varieties from the 3000 Rice Genome Project (3K-RG) were cultivated by hydroponic culture with 0.9% salt solution for trait identification. A genome-wide association study (GWAS) of salt tolerance was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Also, the LD block could show the LD level between each SNP, as well the multiple SNPs make a haplotype block by strong LD level, which is contributed to identified novel haplotype and functional genes. In Yuan's study, they identified multiple strong LD regions in candidate regions using the diverse model and diverse subspecies [66]. Two candidate genes, OsSTL1 and OsSTL2, were identified from strong LD regions in GWAS results.…”
Section: Ld Haplotype and Functional Snp Analysismentioning
confidence: 99%
“…Also, the LD block could show the LD level between each SNP, as well the multiple SNPs make a haplotype block by strong LD level, which is contributed to identified novel haplotype and functional genes. In Yuan's study, they identified multiple strong LD regions in candidate regions using the diverse model and diverse subspecies [66]. Two candidate genes, OsSTL1 and OsSTL2, were identified from strong LD regions in GWAS results.…”
Section: Ld Haplotype and Functional Snp Analysismentioning
confidence: 99%
“…Lekklar et al conducted a GWAS for salt tolerance during rice reproduction, and more than 73% of the identified loci overlapped with the previously reported salt QTLs [92]. Yuan et al performed a GWAS using 664 cultivated rice accessions from the 3000 Rice genomes, and twenty-one salt-tolerant QTLs and two candidate genes were identified [93]. These studies indicate that GWAS is a powerful strategy for mapping QTLs of salt tolerance in rice.…”
Section: Biotechnology Promises To Accelerate Breeding Of Salt-toleramentioning
confidence: 95%
“…In contrast, salt tolerance in varieties like IR29, Fatmawati, Pokkali, Cheriviroppu, FL478, IR651, CSR27, FL30, Fontan, SR86, IR9884-54-3 results from ion exclusion, osmotic and tissue tolerance with multiple genes involved in the process, which confers agronomic stability of this trait (Qin et al, 2020;Reddy et al, 2017;Takagi et al, 2015;. The orchestrated stress system can be targeted for achieving salt tolerance by mutating genes encoding key transcription factors, specifically OsRR22 (Os06g0183100), STL1 (Os04g0110600), and the zinc finger transcription factor encoded by DST (Os03g0786400) (Cui et al, 2015;Santosh Kumar et al, 2020;Yuan et al, 2020;. Other transcription factors are critical in stress adaptation, which results in stress sensitivity when inactivated.…”
Section: Stress Tolerancementioning
confidence: 99%